Pengaruh Persepsi Mahasiswa Tentang Status Sosial Guru Dan Pendidikan Profesi Guru (PPG) Terhadap Motivasi Menjadi Guru Sekolah Dasar - Dyah Indraswati; Prihma Sinta Utami; Suyitno Suyitno; Dodik Kariadi (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2020)
This study aims to determine: (1) the effect of students' perceptions of the teacher's sosial status on student motivation to become a Primary Teachers; (2) the effect of students' perceptions about teacher professional education programs (PPG) on student motivation to become teachers; (3) the effect of students' perceptions about the sosial status of teachers and teacher professional education programs (PPG) on student motivation to become teachers. This research is an ex post facto research with a quantitative approach. The subjects in this study were the 7th-semester students of the University of Mataram's PGSD study program, amounting to 315, then samples were taken using the Slovin formula so that 177 students were obtained. The data collection method uses a questionnaire. Data analysis uses descriptive statistical analysis; analysis prerequisite test consisting of normality test, linearity test, and multicollinearity test; and regression analysis consisting of a simple linear regression test and multiple linear regression test. The results showed: (1) There was a positive and significant influence of students' perceptions about the teacher's sosial status on motivation to become a teacher. (2) There is a positive and significant influence of students' perceptions about PPG on motivation to become a teacher. (3) There is a positive and significant influence of students' perceptions about the sosial status of teachers and PPG simultaneously on the motivation of students to become teachers.